High step‐up Z‐source DC–DC converter with coupled inductors and switched capacitor cell. Issue 8 (1st August 2015) - Poorali, Behzad; Torkan, Arash; Adib, Ehsan
Abstract : Z‐source converter has several advantages such as high‐voltage gain, clamped switch voltage and positive output voltage polarity. This study presents a new non‐isolated high step‐up DC–DC converter which is derived from Z‐source converter and provides higher‐voltage gain compared with its conventional counterpart. Owing to its high‐voltage conversion ratio, the proposed converter is a proper choice for photovoltaic applications. Furthermore, reverse‐recovery problems caused by the output diode are reduced in the proposed converter which reduces the switching losses. In addition, the leakage energy is recycled so the conversion efficiency is improved. Analysis and operating principles of the proposed converter are discussed and design guidelines are presented. Moreover, the effect of non‐ideal elements on the proposed converter performance is analysed. A 100 W laboratory prototype to convert 20–300 V is implemented and experimental results are presented to verify theoretical analysis.